Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1061/(asce)ey.1943-7897.0000673
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Simulation Framework for Assessing Turbocharger Fault Effects on Diesel-Engine Performance and Operability

Abstract: Turbocharged diesel engines are extensively used in marine vessels, both as propulsion engines and as generator sets. The engines operation in the hostile marine environment results to performance degradation having a negative effect on the economics of the marine vessel's operation both in terms of fuel consumption and maintenance. This paper presents a turbocharged 4-stroke diesel engine simulation framework based on one-dimensional calculations and analysis. The framework is suitable for turbomachinery and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The validation has been extensively described in another publication of the group of the authors (Ntonas et al). [12].…”
Section: Turbocharger Retrofitting Platformmentioning
confidence: 99%
See 2 more Smart Citations
“…The validation has been extensively described in another publication of the group of the authors (Ntonas et al). [12].…”
Section: Turbocharger Retrofitting Platformmentioning
confidence: 99%
“…For original turbocharger operation analysis, having measured and using as input the original T/C geometry, in combination with the available shop trials data, the calculation of turbocharged diesel engine operation is performed [12]. The calculated and the measured specific fuel consumption against engine power are presented in Figure 4 for five different operating points (Load: 25, 50, 75, 100 and 110%).…”
Section: Original Turbocharger Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The in-range faults were detected by the second fault detection level by considering localised models where the respective data points were clustered by Gaussian mixture models with an expectation maximisation algorithm. Ntonas et al 11 developed a framework for turbomachinery and heat exchanger components fault simulation for predicting both turbocharger and diesel engine performance and operability by developing a marine four-stroke diesel engine simulation model validated against measured data.…”
Section: Introductionmentioning
confidence: 99%
“…All these techniques, which are actually very effective, currently have the limit of providing for the offline processing of the data obtained in the monitoring and subsequent adjustment of the engine. However, numerous studies [8][9][10][11][12] have demonstrated the possibility of simulating engine operation with remarkable precision.…”
Section: Introductionmentioning
confidence: 99%